Increased immune infiltration and chemokine receptor expression in head and neck epithelial tumors after neoadjuvant immunotherapy with the IRX-2 regimen. (4th May 2018) - Berinstein, Neil L.; McNamara, Michael; Nguyen, Ariane; Egan, James; Wolf, Gregory T.
ABSTRACT: IRX-2 is an injectable cancer immunotherapy composed of cytokines purified from stimulated normal-donor peripheral blood mononuclear cells. In a phase 2a trial (n = 27), neoadjuvant IRX-2 significantly increased lymphocyte infiltration (LI) into resected head and neck tumors and was associated with changes in fibrosis and necrosis. Event-free survival was 65% at 2 years, and overall survival 65% at 5 years. Overall survival was longer for patients with LI greater versus lower than the median. This substudy of the mechanisms responsible for the increase in LI with neoadjuvant IRX-2 employed multiplex immunohistochemistry (IHC) and transcriptome analysis to interrogate matched pre- and post-treatment tumor specimens from 7 available phase 2a trial patients. Multiplex IHC showed substantial increases in CD68-expressing cells (5 patients), T-cell density (4 patients), and PDL1 mean fluorescent intensity (4 patients). Consistent with IRX-2 activation of multiple immune cells, transcriptome analysis showed mean increases in expression of genes associated with NK cells, B cells, CD4 + T cells, CD8 + T cells, and dendritic cells, but not of genes associated with neutrophils. There were increases in mean expression of genes for most immune subsets, most markedly (2- to 3-fold) for B cells and dendritic cells. Mean increases in gene expression for chemokines suggest that tumor LI may be driven in part by IRX-2-induced production of chemo-attractants. Upregulation of checkpoint genes including PDL1 and CTLA4 along with increased T-cell infiltration suggests a functional antitumor immune response such that the efficacy of IRX-2 may be enhanced by combination with immune checkpoint inhibitors.